Analysis of Student Learning Outcomes in Mathematics Learning in View of the Level of Concentration in Learning Building Materials at SDN 93 Singkawang - Sahara, Punam; Utami, Citra; Marhayani, Dina Anika (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This research aims to: Analyze student learning outcomes in Mathematics learning in terms of the level of concentration in learning spatial building material. The type of research used is qualitative research, while the data collection tools used are questions, questionnaires, interviews and documentation. Data collection instruments were mathematics learning outcomes tests and questionnaires on learning concentration levels. The results of the research show that 1) Test student learning outcomes on spatial building material in class V SDN 93 Singkawang. Has an average of 70.37 in the high category (categorized as high because students are able to answer questions well given by the teacher and 2) There are two factors that influence the level of student concentration in class V, namely internal and external. The internal factors are factors that come from within the student as follows: a) physical health problems, b) the emergence of negative feelings, c) not liking certain lessons, d) not having skills in good learning methods, e) weak interest and motivation in lessons, f) be passive in learning. External factors are factors that come from outside, such as: a) a classroom environment that is not conducive, b) the same learning method every day.